A durable and environmental friendly superhydrophobic coatings with self‐cleaning, anti‐fouling performance for liquid‐food residue reduction. Issue 4 (22nd February 2023) - Sun, Yingchun; Liu, Ru; Xu, Jianfeng; Sun, Yuhui; Gong, Jingya; Long, Ling
Abstract: A durable and environmentally‐friendly superhydrophobic coatings for liquid‐food residue reduction were prepared by using stearic acid (SA) modified organic montmorillonite (SA@OMMT) and poly(dimethylsiloxane) (PDMS). Due to the natural hydrophobicity of SAs, SA@OMMT provides low surface energy as well as roughness for the coating. PDMS not only provided low surface energy in the coating but also contributed to the bonding of SA@OMMT as a result of its high adhesive properties. In addition, PDMS has good physical properties after curing, which can effectively improve the physical properties and durability of a superhydrophobic coating by the self‐assembly method using a PDMS/n‐hexane solution. For 1 wt.% SA@OMMT and 5 wt.% PDMS, the resulting SA@OMMT/PDMS (SOP) coating showed the water contact angle (WCA) and water sliding angle (WSA) of 156.3°and 2°, respectively. The prepared coatings have good physical and chemical stability, and they still have superhydrophobicity after physical abrasion tests and exposure to the corrosion solutions. In the meanwhile, the prepared coating also has flexibility and superhydrophobicity after bending and folding. Finally, the coating surface shows highly effective antifouling ability to liquid and solid pollutants. The coating can be applied against different substrates and has potential application in the field of liquid‐food residue reduction. Abstract : Preparation of the superhydrophobic coatings and the self‐cleaning and anti‐fouling performance.